2003
DOI: 10.1099/vir.0.19326-0
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 tegument protein VP22 interacts with TAF-I proteins and inhibits nucleosome assembly but not regulation of histone acetylation by INHAT

Abstract: Affinity chromatography was used to identify cellular proteins that interact with the herpes simplex virus (HSV) tegument protein VP22. Among a small set of proteins that bind specifically to VP22, we identified TAF-I (template-activating factor I), a chromatin remodelling protein and close homologue of the histone chaperone protein NAP-1. TAF-I has been shown previously to promote more ordered transfer of histones to naked DNA through a direct interaction with histones. TAF-I, as a subunit of the INHAT (inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
(38 reference statements)
2
40
0
1
Order By: Relevance
“…Moreover, VP22 from HSV-1 has been shown to interact in vitro with the template-activating factor 1 (TAF-1), a chromatin-remodeling protein and subunit of the INHAT (inhibitor of acetyltransferases) complex. The interaction of VP22 with TAF-1 disrupted the ability of TAF-1 to promote the loading of histones onto naked DNA in vitro (59). These observations raise the hypothesis that VP22 may interfere with nucleosomal deposition on the viral DNA during lytic infection.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, VP22 from HSV-1 has been shown to interact in vitro with the template-activating factor 1 (TAF-1), a chromatin-remodeling protein and subunit of the INHAT (inhibitor of acetyltransferases) complex. The interaction of VP22 with TAF-1 disrupted the ability of TAF-1 to promote the loading of histones onto naked DNA in vitro (59). These observations raise the hypothesis that VP22 may interfere with nucleosomal deposition on the viral DNA during lytic infection.…”
Section: Discussionmentioning
confidence: 67%
“…The finding that the VP22LL251AA mutation, which impaired viral replication and neurovirulence in mice, also attenuated the ability of VP22 to promote the cytoplasmic localization and expression of a number of viral and cellular proteins suggested that these VP22 functions may be critical for viral replication and neurovirulence in vivo. However, the VP22LL251AA mutation may affect a VP22 function(s) other than those identified in this study, since we have not investigated whether Di-Leu-251-252 is required for other VP22 functions, such as functional interaction with microtubules, chromatin, RNA, and cellular membranes (4,17,18,34,43,54,59,66). Further studies to identify other VP22 functions that require Di-Leu-251-252 are needed and are under way in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism(s) by which VP22 acts in viral replication and pathogenesis remains largely unknown at present, a number of functions for VP22 have been reported. These include (i) association with and reorganization of microtubules (18,34); (ii) interaction with chromatin, histones H1 and H4, and template-activating factor 1 (TAF-1), a chromatin-remodeling factor, and impairment of histone acetylation and TAF-1-dependent nucleosome assembly (17,43,54,66); (iii) neutralization of the activity of VHS (62); (iv) binding to a viral RNA and transport of the RNA from cell to cell for expression (59); (v) association with cellular membranes and localization in acidic compartments, including the trans-Golgi network, where HSV-1 nucleocapsids may acquire their final envelope (4,61); (vi) interaction with various viral tegument and envelope proteins, including VP16, ICP0, Us9, UL46, UL47, UL56, glycoprotein E (gE), gD, and gM (7,16,21,22,24,25,35,42,50); (vii) promotion of the synthesis of various viral proteins in infected cells and incorporation of a subset of virion-assembled proteins (13)(14)(15); and (viii) regulation of the compartmentalization of VP16 and ICP0 (15,16). Although many VP22 functions have been clarified, as described above, and the domains responsible for some VP22 functions have been mapped, none of these functions have been explicitly linked to HSV-1 replication and pathogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a growing body of evidence that HSV-1 replication is regulated in part by nucleosome-based mechanisms (reviewed in reference 23). VP22 may promote transcription at late times in infection, when it is present in infected cells in large amounts, via its interactions with the linker histone H1, the core histone H4, or the H2A-H2B-specific histone chaperone template-activating factor I (32,43). Alternatively, VP22 may increase mRNA abundance by protecting it from degradation through its RNA-binding activity (34).…”
Section: Discussionmentioning
confidence: 99%